An assessment of the health knowledge of student health volunteers in the lower secondary schools of educational Region 2, Thailand - Thitipantanma, Supaporn
This study aims to assess the health knowledge of student health volunteers in lower secondary schools in Educational Region 2, Thailand. The instrument used was a criterion-referenced test constructed along five major health areas. It was found out that student health volunteers are little informed in all five major health areas and are most informed with the symptoms of a common cold and least informed with the most significant sign of a shock patient.